SYNTHESIS OF SOME CINNAMIC ACID DERIVATIVES: EFFECT OF GROUPS ATTACHED ON AROMATIC RING TO THE REACTIVITY OF BENZALDEHYDE - Marcellino Rudyanto; Lanny Hartanti (Universitas Gadjah Mada, 2008)
Synthesis of cinnamic acid and its six derivatives has been done by employing Knoevenagel reaction. Benzaldehyde, 4-butylbenzaldehyde, 4-t-butylbenzaldehyde, 4-butoxybenzaldehyde, 4-phenylbenzaldehyde, 5-bromo-2,4-dimethoxybenzaldehyde, and 5-bromo-2,3-dimethoxybenzaldehyde were reacted with malonic acid in pyridine – piperidine to give cinnamic acid (85,3%), 4-butylcinnamic acid (69,3%), 4-t-butylcinnamic acid (77,7%), 4-butoxycinnamic acid (64,5%), 4-phenylcinnamic acid (65,5%), 5-bromo-2,4-dimethoxycinnamic acid (53,2%) and 5-bromo-2,4-dimethoxycinnamic acid (57,2%), respectively. It was disclosed that 4-alkyl, 4-alkoxy, 4-aryl, dan 2-alkoxy groups decrease the reactivity of carbonyl carbon of benzaldehyde.